COVID-19 in childhood: an integrative review (Research, Society and Development, 2022)
Objective: Gather scientific literature to mitigate the spread and reduce the severity of the disease. Methodology: integrative review about COVID-19 infection in pediatric patients using the keywords “COVID-19”, “SARS-CoV-2”, “Child Health” and “Vaccines”. Results: The review consists of 24 scientific articles, selected by inclusion and exclusion criteria. In addition, epidemiological data from the Brazilian Ministry of Health and 2 technical notes issued by Anvisa were used. Discussion: Mild, moderate, severe and critical symptoms were defined, explained through the pathophysiology of the disease that associates the SARS-CoV-2 virus and the renin-angiotensin system (RAS). With this, the form of transmission of this virus and diagnosis was established, which, in addition to the anamnesis and physical examination, uses laboratory tests and tomographic alterations as confirmation of the diagnostic hypothesis. Treatment is directed according to the signs and symptoms presented by the patient, in addition to supplying the body with balanced nutrition and hydration. Prevention takes place through isolation measures to avoid transmission between contacts and with the immunizing agents produced and authorized by Anvisa according to each age group. The acute and severe form that can develop in the pediatric population is the Multisystem Inflammatory Syndrome (MIS-C) causing organ dysfunction and increased inflammatory markers. The treatment of this is based on Kawasaki Disease. Conclusion: COVID-19 infection in the pediatric population can cause direct and indirect effects. Thus, further studies are needed to constantly update protocols that unify prophylactic measures and targeted treatments.